Vegetarian Diet among Athletes on Nutrient Adequacy and Performance: Literature Review - Delita Septia Rosdiana; Fajria Saliha P Prameswari; Putri Novitasari (Universitas Pendidikan Indonesia, 2022)
The objective of this study is to determine the effects of vegetarianism (vegan and semi-vegetarian) among athletes on their nutrient sufficiency and performance. This review is conducted with three steps, namely: literature search and screening; data extraction and analysis; and writing the literature review. The results show that athletes practicing a vegetarian diet may be at a greater risk of nutritional inadequacy especially proteins, essential fatty acids, iron, zinc, calcium, iodine, vitamin D, and vitamin B12. Whilst the effect of vegetarian practice in athletes’ performance has no significant difference with omnivore athletes. vegetarian athletes should plan a well-planned diet to meet the recommendations of macro and micronutrients for the training and recovery phase. At last, vegetarianism in athletes does not affect their performance and their nutritional sufficiency can be maintained by planning well-balanced dietary consumption. Further research is required to broaden our understanding of vegetarianism in athletes